2018
DOI: 10.1038/s41598-018-31619-8
|View full text |Cite
|
Sign up to set email alerts
|

Human susceptibility to social influence and its neural correlates are related to perceived vulnerability to extrinsic morbidity risks

Abstract: Humans considerably vary in the degree to which they rely on their peers to make decisions. Why? Theoretical models predict that environmental risks shift the cost-benefit trade-off associated with the exploitation of others’ behaviours (public information), yet this idea has received little empirical support. Using computational analyses of behaviour and multivariate decoding of electroencephalographic activity, we test the hypothesis that perceived vulnerability to extrinsic morbidity risks impacts susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 87 publications
6
16
1
Order By: Relevance
“…This result fits well with recent finding suggesting that innovation and creativity are strongly associated with affluence and that, on the contrary, harsh and unpredictable environments lead to informational conformism, the tendency to defer to others' judgments (Baumard, 2018, Inglehart, 2018, Jacquet et al, 2018, Nettle, 2018. The basic rationale for this association between environmental harshness and informational conformism is that copying others is cheaper than exploring by oneself, a rationale that has been widely used to study the trade-off between exploration and exploitation in animal foraging (Boyd and Richerson, 1988, Laland and Williams, 1998, Rieucau and Giraldeau, 2011.…”
Section: ))supporting
confidence: 92%
See 2 more Smart Citations
“…This result fits well with recent finding suggesting that innovation and creativity are strongly associated with affluence and that, on the contrary, harsh and unpredictable environments lead to informational conformism, the tendency to defer to others' judgments (Baumard, 2018, Inglehart, 2018, Jacquet et al, 2018, Nettle, 2018. The basic rationale for this association between environmental harshness and informational conformism is that copying others is cheaper than exploring by oneself, a rationale that has been widely used to study the trade-off between exploration and exploitation in animal foraging (Boyd and Richerson, 1988, Laland and Williams, 1998, Rieucau and Giraldeau, 2011.…”
Section: ))supporting
confidence: 92%
“…In line with these ideas, our results show a strong association between per capita scientific production and the activity of parliaments. tendency to defer to others' judgments (Baumard, 2018, Inglehart and Welzel, 2005, Jacquet et al, 2018, Nettle, 2018. This behavioral approach to creativity suggests that individuals in affluent environments should be more innovative in science, but also in all kinds of activities, because the tradeoffs between exploration and social learning are similar (Baumard, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for studying the specific effect of childhood environmental harshness is that it provides an indication that individuals' actual cooperative strategy possibly results from long-term calibration processes. Previous works have already gathered some evidence for the existence of such early calibration in the domains of trust (Hörl et al, 2016;Petersen & Aarøe, 2015), electoral behavior (Safra et al, 2017) and conformist behaviors (Jacquet et al, 2019(Jacquet et al, , 2018. Indeed, the effect of current environmental harshness on life-history strategies and cooperation might simply reflect the flexible adjustment of behavior in response to shortterm variations in local contingencies.…”
Section: Discussionmentioning
confidence: 97%
“…Simpson et al (2012) also found that individuals who had been exposed to unpredictable and rapidly changing environments early in life tended to have more sexual partners and were more risk-seeking at age 23. In addition, recent works have shown an association between current and childhood environmental harshness and trust (Hörl et al, 2016;Petersen & Aarøe, 2015), electoral behavior (Safra et al, 2017) and conformist behaviors (Jacquet et al, 2019(Jacquet et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%